Fish and Wave - Ruzzier, Sergio, 1966- (I can read comics!, 2022)
"When a tiny wave grows bigger and bigger, what's a fish to do? Fish and Wave by Sergio Ruzzier is a playful exploration of what it really means to go with the flow."--